2011
DOI: 10.5194/acp-11-4689-2011
|View full text |Cite
|
Sign up to set email alerts
|

The 2009 stratospheric major warming described from synergistic use of BASCOE water vapour analyses and MLS observations

Abstract: Abstract. The record-breaking major stratospheric warming of northern winter 2009 (January-February) is studied using BASCOE (Belgian Assimilation System for Chemical ObsErvation) stratospheric water vapour analyses and MLS (Microwave Limb Sounder) water vapour observations, together with meteorological data from the European Centre for Medium-Range Weather Forecasts (ECMWF) and potential vorticity (PV) derived from ECMWF meteorological data. We focus on the interaction between the cyclonic wintertime stratosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…The polar vortex descent rate strongly increased around 25 January up to 15 K day −1 on 1000 K and only around 3 K day −1 on 500 K during the late January. The variability of polar vortex descent rate reported here is consistent with findings by Manney et al (2009b) and Lahoz et al (2011) where the tracer isopleths method based on MLS observations of N 2 O, CO and H 2 O was used. The onset of the heating rate anomalies at each altitude, and thus their downward propagation, is roughly synchronous with the temperature anomalies shown in Fig.…”
Section: Dynamical Backgroundsupporting
confidence: 80%
“…The polar vortex descent rate strongly increased around 25 January up to 15 K day −1 on 1000 K and only around 3 K day −1 on 500 K during the late January. The variability of polar vortex descent rate reported here is consistent with findings by Manney et al (2009b) and Lahoz et al (2011) where the tracer isopleths method based on MLS observations of N 2 O, CO and H 2 O was used. The onset of the heating rate anomalies at each altitude, and thus their downward propagation, is roughly synchronous with the temperature anomalies shown in Fig.…”
Section: Dynamical Backgroundsupporting
confidence: 80%
“…The time period of January 2009 was chosen because of the dynamic activity that accompanied the unusually large 2009 Arctic stratospheric major warming (Manney et al, 2009;Lahoz et al, 2011). The winter stratosphere is generally a location with large horizontal ozone gradients, making wind extraction favorable, as explained in Sect.…”
Section: Methodsmentioning
confidence: 99%
“… Randall et al [2006] showed that enhanced descent of NO x into the Arctic vortex occurred after the 2006 SSW, and Randall et al [2009]showed that such enhanced descent coincided with an elevated stratopause in 2006 as well as in other years. It was also shown using satellite observations from the Microwave Limb Sounder (MLS), the Atmospheric Chemistry Experiment ‐ Fourier Transform Spectrometer, and the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument that there was strong descent of various species, including CO and N 2 O, following the reformation of the vortex in 2006 and 2009 [ Manney et al , 2008b, 2009a, 2009b; Lahoz et al , 2011]. Kvissel et al [2011] used WACCM to show this CO rich intrusion from the mesosphere into the middle stratosphere is well correlated with the reformation of the vortex in the lower mesosphere.…”
Section: Introductionmentioning
confidence: 99%